2005
DOI: 10.1175/jcli3360.1
|View full text |Cite
|
Sign up to set email alerts
|

A Look at the Surface-Based Temperature Inversion on the Antarctic Plateau

Abstract: Data from radiosondes, towers, and a thermistor string are used to characterize the temperature inversion at two stations: the Amundsen-Scott Station at the South Pole, and the somewhat higher and colder Dome C Station at a lower latitude.Ten years of temperature data from a 22-m tower at the South Pole are analyzed. The data include 2-and 22-m temperatures for the entire period and 13-m temperatures for the last 2 yr. Statistics of the individual temperatures and the differences among the three levels are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
187
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(264 citation statements)
references
References 30 publications
30
187
2
1
Order By: Relevance
“…Furthermore, the reanalysis indicates that the seasonal cycle in heat flux at Dome F is only 20 W m −2 about a mean consistent with the Antarctic average, suggesting that a constant heat convergence is a reasonable approximation for this site, though the annual cycle in the reanalysis is larger at other sites (for example 140 W m −2 at Dome C). The seasonal cycle in temperature produced by SCAM is similar to observations, including reproduction of a thermal inversion layer with an average magnitude of ∼15 • C and a seasonal amplitude of ∼50 • C within the troposphere 25 .…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the reanalysis indicates that the seasonal cycle in heat flux at Dome F is only 20 W m −2 about a mean consistent with the Antarctic average, suggesting that a constant heat convergence is a reasonable approximation for this site, though the annual cycle in the reanalysis is larger at other sites (for example 140 W m −2 at Dome C). The seasonal cycle in temperature produced by SCAM is similar to observations, including reproduction of a thermal inversion layer with an average magnitude of ∼15 • C and a seasonal amplitude of ∼50 • C within the troposphere 25 .…”
Section: Methodssupporting
confidence: 70%
“…Note that the peculiarities of the Antarctic climate represented in SCAM seem to make local radiative balance an important control on temperature. A strong thermal inversion layer exists over Antarctica for most of the year 25 because the ice surface emits radiation more efficiently than the atmosphere. As a result, convection and the exchange of heat between the troposphere and the ice surface is inhibited.…”
Section: Radiative Equilibrium and The Duration Of Summermentioning
confidence: 99%
“…In this study, we therefore employ a gap-filling procedure with ERA-Interim nearsurface air temperatures. During cloudy periods, reanalysisderived air temperatures may indeed facilitate an adequate representation of surface temperatures, as the near-surface temperature gradient is smaller compared to clear-sky conditions (e.g., Hudson and Brandt, 2005;Gallo et al, 2011;Westermann et al, 2012). As demonstrated by Westermann et al (2015) for the N Atlantic region, the composite product features a considerably reduced bias and is significantly better suited as input for permafrost modeling than the original MODIS LST record.…”
Section: Surface Temperaturementioning
confidence: 99%
“…In contrast, due to the mere shortage of insolation (and high surface albedo), the surface inversions over the polar regions are of long-lived (aka persistent) nature. Based on ten years of temperature data at the South Pole, Hudson and Brandt (2005) found that the lapse conditions within a near-surface layer (2-22 m) were observed only 26% and 8% of the time during austral summer and winter, respectively. They also reported that throughout these years no signatures of diurnal cycles were found at the South Pole.…”
Section: A Brief Comparison Of Polar and Mid-latitude Sblsmentioning
confidence: 99%